Sons of a Minor God: Use of Reproductive Techniques by Single People and Gay Couples. - DOI:10.5935/2448-0517.20170015 - Raposo, Vera Lúcia (Juris Poiesis - Qualis A3, 2017)
The progressive recognition of new family units (monoparental and same-sex families) as objects of legal protection is the product of enormous changes in society and in the way we understand our sexual choices. One of the consequences of this societaltransformationinvolves access to assisted reproductive techniques (ART). Access to ART is traditionally allowed only for married people (obviously of the opposite gender, asopposite-sex marriage is still the regular standard and the only legal option in many parts of the world).Access to ART is sometimes allowed for heterosexual couples living in a de facto relationship. Today, some legal systems already permit the use of ART by single people and gay couples. Brazil is a good example, but in the remaining Latin-American countries as well as in Asia, restrictive solutions take precedence, although in most cases there is no proper regulation regarding ART. Most legal systems around the world still impose restrictions based on marital status and/or sexual orientation. Such legal prohibitions are problematic from a juridical perspective. In fact, it is recognised that reproduction is a fundamental right and a human right (instead of a mere aspiration or a whim), as has been stated by various courts around the world, including the Inter-American Court of Human Rights. This conclusion also results from the interpretation of some rights expressly recognised in national constitutions - namely, the right to privacy and the right to create a family - as including reproduction withintheir scope of protection, leading to the conclusion that reproduction is actually a constitutionally protected right. If this is so, any restriction on access to ART is actually limiting the fundamental right to reproduce, which can only be legally limited in the face of a particularly strong justification, such as the protection of the rights of others or of prominent constitutional values. To avoid criticism on constitutional grounds, the supporters of restrictive access to ART have invoked an apparently unbeatable argument: the protection of the future child. These advocates claim that if the child were born into a monoparental family or moreover into a same-sex family,then its well-being would be jeopardisedand its rights violated. However, this argument does not withstand strict constitutional scrutiny, as on the one hand it is too simplistic to justify limitations to constitutionally protected and fundamental rights and on the other hand no one has thus far adequately defineda "child's best interest".This paper intends to demonstrate that these are largely moral arguments that have no juridical foundations andare therefore incapable of attaching limitations to reproductive rights.